Gender-specific prevalence of sacrococcygeal pilonidal sinus disease in Turkey: A retrospective analysis of a large cohort - UPRAK, TEVFİK KIVILCIM (My University, 2022)
Background Many studies have been carried out to find the optimal treatment for pilonidal sinus disease (PSD), but the gender-specific prevalence in Turkey has not been revealed. Therefore, this article evaluated patients diagnosed with pilonidal sinus disease in our hospital. We aimed to analyze the gender ratio in PSD. Methods We evaluated patients admitted and who underwent pilonidal sinus excision at the Istanbul Sultanbeyli State Hospital between January 2010 and January 2022. Patients with missing data, multiple admissions, and multiple surgeries of the same patient were excluded from the analyses. Patients were stratified according to age into two groups: = 18 (adult). Age and gender, diagnosis at admission, and operation status were analyzed. Results A total of 10,324 PSD patients were analyzed. 24.8% (n = 2559) of the patients were female and 75.2% (n = 7765) were male. Patients\" ages ranged from 13 to 86 years; the mean age was 26.5 years. Of all patients, 1621 (15.7%) had an abscess at the time of diagnosis. 4345 pilonidal sinus surgery cases were evaluated; 25.3% (n = 1100) of the patients were female and 74.7% (n = 3245) were male. The girl/boy ratio of PSD in teenagers was 0.86, and the female/male ratio of PSD in patients aged 18 years and older was 0.27. Conclusion The female gender prevalence of sacrococcygeal pilonidal sinus disease is 25% in Turkey. Pilonidal sinus disease surgery is mainly performed in secondary care hospitals; therefore, unpublished data from these centers may contribute more to pilonidal sinus disease research.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; Pilonidal sinus; Pilonidal sinus disease; Hair; Epidemiology; Gender medicine; Turkish population; Pilonidal cyst; EXPERIENCE